Variasi Bentuk Lengkung Longitudinal Medial Kaki pada Laki-Laki dan Perempuan Dewasa Muda - Pasaribu, Saadatur Rizqillah; Siregar, Nondang Purnama; Pasaribu, Rifqi Hamdani; Sari, Siti Kemala; Adnani, Athika (Universitas HKBP Nommensen, 2025)
The medial longitudinal arch is a part of the plantar foot with clinical significance. Three variations of the medial longitudinal arch consist of normal, low, and high arches. These variations are caused by intrinsic factors such as gender. Failure to form the normal medial longitudinal arch leads to poor posture and balance. Variation in the shapes of the medial longitudinal arch can be assessed using footprints, namely the arch index. This study aims to identify the variations in the medial longitudinal arch between young adult males and females. The research is descriptive-analytic with a cross-sectional study design. The subjects are young adults aged 18-22 years. Sampling using the simple random sampling technique with a sample size of 54 participants. The medial longitudinal arch shape was evaluated using the footprint method with the arch index. The majority of participants (72.2%, 39 participants) were female, according to the results. The most age group was 21 years old 23 participants (42.6%). The highest average arch index (0.29) was in the male participants. The most prevalent normal medial longitudinal arch shape was observed in females 28 participants (71.8%). In males, the low arch was most common among 11 participants (73.35%), while the high arch was found in 5 female participants (12.8%). The Mann-Whitney statistical test showed p < 0.05. This study concludes that the medial longitudinal arch forms vary between young adult males and females.